Evaluation of NR52 GPS Receivers in Geodesy - Fourgassie, Alain (The International Hydrographic Review, 2015)
EPSHOM acquired two NR52 GPS receivers in March 1988. These receivers, marketed by SERCEL, have been specially designed lor geodesy and determination of the trajectory of moving points. The GPS Mission programme, also distributed by SERCEL, makes it possible to process data recorded by these receivers for geodetic purposes. Prior to their operational deployment by SHOM’s hydro-oceanographic teams, this equipment and the programme were evaluated by EPSHOM. It became evident that the existing geodetic network was not sufficiently accurate to constitute a valid reference. It was, therefore, the repeatability criteria which was chosen to evaluate the accuracy of the measurements obtained by the GPS system. The results vary between 1 and 4 ppm for baselines from 0 to 130 km in length.